2015
DOI: 10.1007/s00586-015-3801-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring lumbar plexus integrity in extreme lateral transpsoas approaches to the lumbar spine: a new protocol with anatomical bases

Abstract: A detailed IOM of lumbar plexus branches can determine in real time the proximity of intrapsoas nerves during XLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…This is posited to be a result of upper lumbar plexopathy secondary to stretch injury through retraction or sensory nerve injury on approach (50). Groin and thigh hyperesthesia is likely the result of injury to the iliohypogastric or ilioinguinal nerve during preparation through the abdominal wall with hyperesthesia usually spontaneously resolving (51).…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is posited to be a result of upper lumbar plexopathy secondary to stretch injury through retraction or sensory nerve injury on approach (50). Groin and thigh hyperesthesia is likely the result of injury to the iliohypogastric or ilioinguinal nerve during preparation through the abdominal wall with hyperesthesia usually spontaneously resolving (51).…”
Section: Complicationsmentioning
confidence: 99%
“…Dakwar et al (52) and Oliveira et al (53) reported transient postoperative anterior thigh numbness, ipsilateral to the side of approach in 12% and 14.3% of cases respectively. Short-term thigh dysthanasia and hip flexor weakness are well documented due to direct trauma to the psoas muscle yet quickly resolve in most cases (50). Longer psoas retraction time has been associated with lumbar plexopathy thought to be due to nerve compression and/or stretch (41).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMG monitoring throughout the surgical procedure is therefore mandatory. A new neurophysiological monitoring method that includes EMG and transpsoas stimulation to accurately evaluate the proximity of every branch of the lumbar plexus has been recently developed [29]. Indirect mechanisms may also contribute to determine a traction injury of the femoral nerve.…”
Section: Femoral Nervementioning
confidence: 99%
“…However, the standard lateral approach, which traverses the psoas muscle (i.e., transpsoas approach), has its own limitations and complications (2)(3)(4)(5)(6). Of most concern is the potential for injury to the lumbar plexus, minimized by using intraoperative neuromonitoring (7). An alternative approach, anterior to psoas (ATP), without neuromonitoring, has been described (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%